Adolescent Girls’ Understanding of Tetanus Infection and Prevention: Implications for the Disease Control in Western Nigeria - Orimadegun, Adebola E.; Adepoju, Akinlolu A.; Akinyinka, Olusegun O. (Frontiers in Public Health, 2014)
Tetanus is a major cause of morbidity and mortality in developing countries. Nigeria is aiming to eliminate tetanus by maintaining coverage of routine vaccinations for infants and pregnant women, but little attention is given to the adolescents’ needs. This study assessed the understanding of adolescent girls about tetanus infection and prevention in order to provide information that may foster better policy. In this cross-sectional analytical study, 851 female adolescents were selected from eight secondary schools in Ibadan, south-west of Nigeria using a three-stage random sampling technique. A pre-tested structured questionnaire was used to obtain information on demographic and socio-economic characteristics, history of tetanus vaccination and adolescents’ knowledge of tetanus infection. Mean age of respondents was 14.3±1.9 years. Only 3.1% had received tetanus toxoid injection one year prior to the study, most frequently following a “wound or injury” (65.4%). Though, 344 (40.4%) respondents claimed they knew tetanus as a “serious neurological disease”, only 46.5% correctly defined tetanus. Overall, the mean knowledge score was 4.8±3.1 and 64.7% of the respondents had poor knowledge. Academic class was significantly associated with knowledge; higher mean score among the senior (5.3±5.3) than junior classes (4.4±3.2); p< 0.001. Over half (56.2%) of the adolescents disagreed with the statement that “tetanus immunisation can be given to students in the school premises”. There is the need to improve immunisation campaigns against tetanus among adolescent girls and consider the introduction of school-based immunisation programmes if the elimination of maternal and neonatal tetanus is to be achieved.